Bureau Clergyman: How the FBI Colluded with an African American Televangelist to Destroy Dr. Martin Luther King, Jr. - Martin, Lerone A. (Religion and American culture, 2018)
This article explains how the Federal Bureau of Investigation (FBI) partnered with African American minister Elder Lightfoot Solomon Michaux to discredit and neutralize Reverend Martin Luther King Jr. The Elder, the nation's first minister (black or white) to have his own weekly television show, colluded with the Bureau to shape public opinion against King and cast doubt upon King's religious commitments and activities. Michaux was, what I call, a Bureau Clergyman: a minister who was an FBI Special Service Contact or on the Bureau's Special Correspondents Lists. Far from secret informants, black and white male clergy in these official Bureau programs enjoyed very public and cooperative relationships with the FBI and were occasionally called into service to work in concert with the FBI. The FBI called upon Michaux and he willingly used his status, popular media ministry, and cold war spirituality to publically scandalize King as a communist and defend the Bureau against King's criticisms. In the end, the Elder demonized King, contested calls for black equality under the law, and lionized the FBI as the keeper of Christian America. The story moves the field beyond the very well known narratives of the FBI's hostility towards religion and reveals how the Bureau publicly embraced religion and commissioned their clergymen to help maintain prevailing social arrangements. Michaux's relationship with the FBI also offers a window into the overlooked religious dimensions of the FBI's opposition to King, even as it highlights how black clergy articulated and followed competing ideologies of black liberation during the civil rights movement.